Interplay of Gut Microbiota in Polycystic Ovarian Syndrome: Role of Gut Microbiota, Mechanistic Pathways and Potential Treatment Strategies - Leander Corrie; Ankit Awasthi; Jaskiran Kaur; Sukriti Vishwas; Monica Gulati; Indu Pal Kaur; Gaurav Gupta; Nagavendra Kommineni; Kamal Dua; Sachin Kumar Singh (MDPI AG, 2023)
Polycystic Ovarian Syndrome (PCOS) comprises a set of symptoms that pose significant risk factors for various diseases, including type 2 diabetes, cardiovascular disease, and cancer. Effective and safe methods to treat all the pathological symptoms of PCOS are not available. The gut microbiota has been shown to play an essential role in PCOS incidence and progression. Many dietary plants, prebiotics, and probiotics have been reported to ameliorate PCOS. Gut microbiota shows its effects in PCOS via a number of mechanistic pathways including maintenance of homeostasis, regulation of lipid and blood glucose levels. The effect of gut microbiota on PCOS has been widely reported in animal models but there are only a few reports of human studies. Increasing the diversity of gut microbiota, and up-regulating PCOS ameliorating gut microbiota are some of the ways through which prebiotics, probiotics, and polyphenols work. We present a comprehensive review on polyphenols from natural origin, probiotics, and fecal microbiota therapy that may be used to treat PCOS by modifying the gut microbiota.